Influence of intensified adherence counselling on viral load suppression of people receiving antiretroviral therapy at a health centre IV in southwestern Uganda: a qualitative study - Pius, Atwau; Josephine, Najjuma Nambi; Erick, Sibo; Winifred, Agoa; Rita, Mukashyaka; Silverjoseph, Okoli; Lucy, Ezatiru; Novatus, Nyemara (AIDS Research and Therapy, 2021)
Background: The prevalence of Human Immunodeficiency Virus (HIV) among adults and children in Uganda is 6.2% and 0.5% respectively. The prevalence of viral load suppression in Uganda among all adults and children living with HIV is 59.6% and 39.3% respectively. High viral load compromises on the quality of life of an individual, and as well increases on the risk of transmission of the virus to the unborn for pregnant mothers and to the spouse. The UNAID 90-90-90 campaign recommends that 90% know their status, 90% get treatment and 90% have viral suppression. Non-adherence to Antiretroviral Therapy (ART) is one of the causes of the high viral load. The world health organization recommends Intensified Adherence Counselling (IAC) be given to all individuals with a high viral load. The perceptions, attitudes and practices of people receiving IAC is important in understanding how best IAC should be implemented. Methods: A qualitative study was done among 30 purposively selected individuals/guardians of children receiving ART and IAC at Kyabugimbi Health Center Four [HC IV (mini-hospital headed by a medical doctor)]. Data collected from Focus Group Discussion as audio-recordings in local language (Runyankole) was transcribed and later translated into English. Translated transcripts were analyzed manually using thematic content analysis. Results: The major themes identified include: adherence to ART; change of attitude towards ART after IAC, IAC expectation and outcomes, IAC and stigma, and improving social support through IAC for PLWHIV. Conclusion: Participating in IAC to be informative and led to change in their perceptions of HIV and better understanding the reasons for adherence to ART. IAC influenced the change in attitude and behavior thus seeking social support and mitigate stigma, which lead to a better ART adherence. However, there is need to improve on the way it is delivered both in structural setting and break down and packaging of information.
Keywords: ART; Uganda; Adherence perceptions; Attitudes; Practices; Intensified Adherence Counseling (IAC)